Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXV: 2021 - Maria; Magdalena; Francesca Panini (Aethiopica)
Bibliography of Ethiopian Semitic, Cushitic, and Omotic Linguistics XXV: 2021